Effect of Carbon Overcoat Implantation on the Magnetic and Structural Properties of Perpendicular Recording Media - Piramanayagam, S. N. (2016)
Carbon overcoats play an important role in the corrosion protection of recording media used in hard disk drive technology. Filtered-cathodic vacuum arc (FCVA) has been studied in the past as a potential technology for depositing media overcoat. In order to achieve the desired property of FCVA carbon, it is essential to apply a suitable bias voltage, which results in an energetic carbon deposition on the magnetic layer of the recording media. In this paper, we focus our attention on the implantation effects of the energetic carbon on the magnetic and the structural properties of the recording media of two types, antiferromagnetically coupled and a single layer, in order to gain a meaningful insight on the implantation and its effect. The studies reveal that the energetic deposition alters the anisotropy constant of the magnetic layer, resulting in a reduction in the coercivity and the thermal stability factor.